DESAIN DAN VALIDASI MODEL BASIS DATA PEMELIHARAAN KOMPONEN ARSITEKTUR GEDUNG SEBAGAI PENDUKUNG FACILITY MAINTENANCE MANAGEMENT (FMM) - Santosa, Stefanus; Suroso, Suroso; Suwarto, Suwarto; Setiyono, Karnawan Joko; Suwarno, Anung (Wahana Teknik Sipil: Jurnal Pengembangan Teknik Sipil, 2024)
The problems that arise in Facility Maintenance Management (FMM) in Indonesia, which involve aspects of management, learning, and mutual understanding in the Common Data Environment (CDE), can be overcome one way by developing a database. To compile a good database, a database design method is required that is based on existing theories and standards. This research was conducted to design a database model with the scope of the object of architectural component maintenance of buildings starting from the stages of identifying needs, designing, and testing to users. The results of the study show that the database model obtained has the category of "very feasible" overall or partially in terms of service quality and material aspects. This also proves that proven methods and design techniques in providing accurate, non-overlapping, and efficient information needed in the management of material data, equipment, contractors, types of work, schedules, and costs during the maintenance and maintenance of architectural component buildings can be met properly through a relational database approach and verification and validation testing. For the development of science, especially Computational of Building Modeling Learning Technology, the results of this research provide a contribution in the form of a Database Model for Architectural Component Maintenance that can be applied in industry and education. It is recommended that this database design model be further developed into a Building Architectural Component Maintenance Information System.